An efficient access to the synthesis of novel 12-phenylbenzo[6,7]oxepino[3,4-b]quinolin-13(6H)-one derivatives - Gao, Wentao; Lin, Guihai; Li, Yang; Tao, Xiyue; Liu, Rui; Sun, Lianjie (Beilstein Journal of Organic Chemistry, 2012)
An efficient access to the tetracyclic-fused quinoline systems, 12-phenylbenzo[6,7]oxepino[3,4-b]quinolin-13(6H)-one derivatives 4a–l, is described, involving the intramolecular Friedel–Crafts acylation reaction of 2-(phenoxymethyl)-4-phenylquinoline-3-carboxylic acid derivatives 3a–l aided by the treatment with PPA (polyphosphoric acid) or Eaton’s reagent. The required starting compound (2) was obtained by Friedländer reaction of 2-aminobenzophenone (1) with 4-chloroethylacetoacetate by using CAN (cerium ammonium nitrate, 10 mol %) as catalyst at room temperature. The substrates 3a–l were prepared through one-pot reaction of ethyl 2-(chloromethyl)-4-phenylquinoline-3-carboxylate (2) and substituted phenols. Our developed strategy, involving a three-step route, offers easy access to tetracyclic-fused quinoline systems in short reaction times, and the products are obtained in moderate to good yields.
Keywords: Eaton’s reagent; Friedel–Crafts acylation; Friedländer reaction; one-pot; PPA; quinoline; tetracyclic-fused